Protocol evaluating the effectiveness of a school-based group programme for parents of children at risk of ADHD: The 'PArents, Teachers and CHildren WORKing together (PATCHWORK)' cluster RCT protocol - Sayal, Kapil; Daley, David; James, Marilyn; Yang, Min; Batty, Martin J.; Taylor, John A.; Pass, Sarah; Sampson, Christopher James; Sellman, Edward; Valentine, Althea; Hollis, Chris (BMJ Publishing Group, 2012)
Introduction Early intervention for childhood behavioural problems may help improve health and educational outcomes in affected children and reduce the likelihood of developing additional difficulties. The National Institute for Health and Clinical Excellence guidelines for attention deficit/hyperactivity disorder (ADHD), a common childhood behavioural disorder, recommend a stepped care approach for the identification and management of these problems. Parents of children with high levels of hyperactivity and inattention may benefit from intervention programmes involving behavioural management and educational approaches. Such interventions may be further enhanced by providing training and feedback to teachers about the strategies discussed with parents. In relation to children with high levels of hyperactivity, impulsiveness and inattention, we aim to test the feasibility and effectiveness of a parenting programme (with and without an accompanying teacher session) in primary schools.